Antimicrobial Activity and Mechanism of Polyvinyl Chloride Composite Containing Inorganic Bacteriocide - Park, Se-Ho; Lee, Jae-Yeul; Choi, Ju-Hwan; Park, Tae-Hee; Moon, Sung-Bae; Lee, Hyeongsu; Bang, Daesuk; Yang, Seun-Ah; Jhee, Kwang-Hwan (Elastomers and composites, 2015)
Bacterial infection is one of the most common and universal cause of disease spreading associated with medical and surgical environment. Antimicrobial function of plasticized polyvinyl chloride (PVC) will be useful for making hygienic environments. Here, we synthesized the PVC composite by the addition of inorganic bacteriocide containing silver, zinc and zeolite. And we investigated the growth inhibition rate for Staphylococcus aureus and Klebsiella pneumoniae which were analyzed in the presence of PVC composite with different doses of inorganic bacteriocide (1~15 wt%). Bacterial proliferation was significantly inhibited by 3 wt% of inorganic bacteriocide containing PVC composite. And we found the inhibition of bacterial biofilm formation by 5 wt% of inorganic bacteriocide containing PVC composite by the observation of scanning electron microscopy (SEM). Our data suggested that the antimicrobial effect of inorganic bacteriocide was caused by disturbing the bacterial biofilm formation.